сын Бе'ора: VDI 208 (1/1994) 99-134 [engl. Untertitel - Шифман, И.. Билеам
Šifman, I., Bile'am, son Be'or; engl. Untertitel: From the History of Socio-Political and Literary Life of the Near Eastern Mediterranean in the First Half of the 1st Millennium B.C.